Studies in Conversational UX Design - Moore, Robert J; Szymanski, Margaret H; Arar, Raphael; Ren, Guang-Jie (Human–Computer Interaction Series, 2018)
As voice interfaces and virtual assistants have moved out of the industry research labs and into the pockets, desktops and living rooms of the general public, a demand for a new kind of user experience (UX) design is emerging.